2009
DOI: 10.2174/1876506800902020033
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Pregnancy Loss and Thrombophilia

Abstract: Emerging data seem to be available also on the role of active thromboprophylaxis with heparin and pregnancy outcome. In the last decades we found many data concerning the association between a hypercoagulable state and its causes and adverse pregnancy outcome, in particular recurrent pregnancy loss (RPL). First studies which focused on the association between thrombophilia and RPL underlined the role of reduced clotting inhibitors and RPL, and subsequent studies underlined a pathogenetic role of gene variant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
3
18
0
Order By: Relevance
“…In addition, the ACE I/D polymorphism has been found to be associated with the disease and the hypofibrinolytic disorders [11,12]. Although the exact factors for RPL are not confirmed, the inherited predisposition to thrombophilia may be one of the main causes according to some studies [13][14][15][16][17].…”
Section: Diseasementioning
confidence: 99%
“…In addition, the ACE I/D polymorphism has been found to be associated with the disease and the hypofibrinolytic disorders [11,12]. Although the exact factors for RPL are not confirmed, the inherited predisposition to thrombophilia may be one of the main causes according to some studies [13][14][15][16][17].…”
Section: Diseasementioning
confidence: 99%
“…Importantly, numerous studies have already proven the existence of a correlation between inherited thrombophilia and pregnancy loss [1][2][3][4][5][6]. Standard diagnostic testing for thrombophilia in these patients involves factor V Leiden, 677C>T MTHFR gene polymorphism, 20210G>A prothrombin gene polymorphism, protein C, protein S and antithrombin deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported increasing evidence for a pathogenetic role of MTHFR gene polymorphism C677T in recurrent pregnancy loss, in particular, early loss. [9][10][11] On the other hand, other authors found a negative association stating that MTHFR polymorphisms do not carry any risk in pregnancy. 12,13 The different inclusion criteria and the different ethnic backgrounds of the selected patients may have contributed to the contradictory results.…”
Section: Discussionmentioning
confidence: 96%
“…The same results were reported by previous studies that identified combined thrombophilic defects in women with recurrent pregnancy loss, both early and late. 10,18,19 The study by Rozano-Gorelick et al reported that combined thrombophilia exists when inherited and /or acquired prothrombotic factors are pooled and every combination carries a different risk of thrombosis. 18 Furthermore, Sarig et al proposed a scoring system for women with thrombophilia based on four major categories: obstetric history, previous thromboembolic events, family history of thrombosis or gestational vascular complications and type of thrombophilia.…”
Section: Discussionmentioning
confidence: 99%